3(x-2)-4(x+1)=

Simple and best practice solution for 3(x-2)-4(x+1)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(x-2)-4(x+1)= equation:


Simplifying
3(x + -2) + -4(x + 1) = 0

Reorder the terms:
3(-2 + x) + -4(x + 1) = 0
(-2 * 3 + x * 3) + -4(x + 1) = 0
(-6 + 3x) + -4(x + 1) = 0

Reorder the terms:
-6 + 3x + -4(1 + x) = 0
-6 + 3x + (1 * -4 + x * -4) = 0
-6 + 3x + (-4 + -4x) = 0

Reorder the terms:
-6 + -4 + 3x + -4x = 0

Combine like terms: -6 + -4 = -10
-10 + 3x + -4x = 0

Combine like terms: 3x + -4x = -1x
-10 + -1x = 0

Solving
-10 + -1x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '10' to each side of the equation.
-10 + 10 + -1x = 0 + 10

Combine like terms: -10 + 10 = 0
0 + -1x = 0 + 10
-1x = 0 + 10

Combine like terms: 0 + 10 = 10
-1x = 10

Divide each side by '-1'.
x = -10

Simplifying
x = -10

See similar equations:

| x=-1/2 | | x=-1/2 | | y^2-4y=4 | | 6y-4=2y+10 | | 3x+39=13x-37 | | 2a^2-12a+18=14 | | a-8=13 | | x^2+20x=9 | | h=25-9t | | 6(x+5)-(4x-5)= | | 9y-5=7+8y | | 240000=80x | | 6-(3x-3)-[2(-4x-1)]=-(-3x+2) | | 4y=15-y | | 9y-5(y-2)=12 | | 2x^3-x^2-3x+1=0 | | -x^4+5x^3+3x^2-13x=10 | | 699=c*(1+.30) | | 699=c*.30 | | 160=t^2 | | 1500x=120000 | | 262=h^2 | | 7x^2=847 | | x^2+6-4=0 | | Q=40-2P | | 9m-4=-(18)+2m | | 6x+5=2x+-3 | | 6x-7x-3=15 | | y=4(1) | | 4b^2=256 | | 4y-(2y-1)=7 | | x^2+2x-143=0 |

Equations solver categories